Minimum Wages and the Gender Gap in Pay: New Evidence from the UK and Ireland - Olivier Bargain; Karina Doorley; Philippe Van Kerm (Institute of Labor Economics (IZA), 2018)
Women are disproportionately in low paid work compared to men so, in the absence of rationing effects on their employment, they should benefit the most from minimum wage policies. This study examines the change in the gender wage gap around the introduction of minimum wages in Ireland and the United Kingdom. Using survey data for the two countries, we develop a decomposition of the change in the gender differences in wage distributions around the date of introduction of minimum wages. We separate out 'price' effects attributed to minimum wages from 'employment composition' effects. A significant reduction of the gender gap at low wages is observed after the introduction of the minimum wage in Ireland while there is hardly any change in the UK. Counterfactual simulations show that the difference between countries may be attributed to gender differences in non-compliance with the minimum wage legislation in the UK.
Keywords: C14; I2; J16; 330; gender wage gap; minimum wage; distribution regression